Research on loss rules of oil and gas in preserved shale cores after open air exposure - Zhang, Jinyou; Wang, Min; Li, Jinbu; Liu, Zhao; Xu, Liang (Frontiers in Earth Science, 2024)
There is a large amount of oil and gas loss in traditional conventional core samples.Revealing the rules of oil and gas loss is of great significance for restore the pristine oil content and oil component in the shale. In this study, 4 preserved shale cores with different thermal maturity (Ro Ro = 1.01-1.53%) and different total organic carbon content (TOC = 1.69-5.48 wt.%) were selected.The samples are obtained from the first member of the Qingshankou Formation in the Gulong Sag.Nuclear magnetic resonance (NMR) T1-T2T1-T2 mapping and thermal desorption gas chromatography (TD-GC, at a constant temperature of 300 °C for 3 min) were performed on the fresh preserved cores and their replicas that were exposed in open air for different times, to study dynamic loss process and the molecular composition changes of shale oil. The results show that during exposure, shale experiences a large amount of oil loss, with a loss ratio of about 42% to 78%, and the higher the maturity, the greater the loss ratio. The oil loss is mainly contributed by free oil, with a loss ratio as high as 88%., The adsorbed oil content, however, remains basically unchanged and has a good positive correlation with the TOC of shale. Once the cores were crushed, the gaseous hydrocarbon in oil was basically evaporated in just 5 minutes. After long-term storage, 90% of the C14-light hydrocarbon is lost, while the C14+ heavy hydrocarbon experiences basically no loss.Therefore, effective and timely analysis of preserved shales is extremely important. The oil content of uncrushed shale cores characterized by NMR T1-T2T1-T2 mapping is much greater than that of the crushed sample measured by TD-GC, which means that NMR T1-T2T1-T2 mapping can be important method to evaluate the original fluid saturation of shale.